Nucleotide Analog ARL67156 as a Lead Structure for the Development of CD39 and Dual CD39/CD73 Ectonucleotidase Inhibitors - Schäkel, Laura; Schmies, Constanze C.; Idris, Riham M.; Luo, Xihuan; Lee, Sang-Yong; Lopez, Vittoria; Mirza, Salahuddin; Vu, The Hung; Pelletier, Julie; Sévigny, Jean; Namasivayam, Vigneshwaran; Müller, Christa E. (Frontiers in Pharmacology, 2020)
Nucleoside triphosphate diphosphohydrolase1 (NTPDase1, CD39) inhibitors have potential as novel drugs for the (immuno)therapy of cancer. They increase the extracellular concentration of immunostimulatory ATP and reduce the formation of AMP, which can be further hydrolyzed by ecto-5’-nucleotidase (CD73) to immunosuppressive, cancer-promoting adenosine. In the present study, we synthesized analogs and derivatives of the standard CD39 inhibitor ARL67156, a nucleotide analog which displays a competitive mechanism of inhibition. Structure-activity relationships were analyzed with respect to substituents in the N6- and C8-position of the adenine core, and modifications of the triphosph(on)ate chain at the human enzyme. Capillary electrophoresis coupled to laser-induced fluorescence detection employing a fluorescent-labeled ATP derivative was employed to determine the compounds’ potency. Selected inhibitors were additionally evaluated in an orthogonal, malachite green assay versus the natural substrate ATP. The most potent CD39 inhibitors of the present series were ARL67156 and its derivatives 31 and 33 with Ki values of around 1 µM. Selectivity studies showed that all three nucleotide analogs additionally blocked CD73 acting as dual-target inhibitors. Docking studies provided plausible binding modes to both targets. The present study provides a full characterization of the frequently applied CD39 inhibitor ARL67156, presents structure-activity relationships, and provides a basis for future optimization towards selective CD39 and dual CD39/CD73 inhibitors.